1999
DOI: 10.1093/hmg/8.12.2191
|View full text |Cite
|
Sign up to set email alerts
|

A Missense Mutation in the Desmin Rod Domain Is Associated with Autosomal Dominant Distal Myopathy, and Exerts a Dominant Negative Effect on Filament Formation

Abstract: In some myopathies of distal onset, the intermediate filament desmin is abnormally accumulated in skeletal and cardiac muscle. We report the first point mutation in desmin cosegregating with an autosomal dominant form of desmin-related myopathy. The L345P desmin missense mutation occurs in a large, six generation Ashkenazi Jewish family. The mutation is located in an evolutionarily highly conserved position of the desmin coiled-coil rod domain important for dimer formation. L345P desmin is incapable of forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1
5

Year Published

2001
2001
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 32 publications
2
84
1
5
Order By: Relevance
“…83 It has been conclusively shown that pathogenic mutant desmin disrupts a preexisting filamentous network in a dominant-negative fashion. 6,53,84 But some mutations located in the nonalpha-helical tail domain of the desmin molecule do not interfere with the initial IF assembly steps. Thus, the p.Thr442Ile, p.Lys449Thr, p.Ile451Met and p.Val469Met mutants, but not p.Arg454Trp and p.Ser460Ile, formed a filamentous network in SW13 cells.…”
Section: Filament and Network Assembly Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…83 It has been conclusively shown that pathogenic mutant desmin disrupts a preexisting filamentous network in a dominant-negative fashion. 6,53,84 But some mutations located in the nonalpha-helical tail domain of the desmin molecule do not interfere with the initial IF assembly steps. Thus, the p.Thr442Ile, p.Lys449Thr, p.Ile451Met and p.Val469Met mutants, but not p.Arg454Trp and p.Ser460Ile, formed a filamentous network in SW13 cells.…”
Section: Filament and Network Assembly Studiesmentioning
confidence: 99%
“…37,46,55 Skeletal muscle weakness followed by cardiomyopathy was observed in 31 patients from 20 families ( Table 2). A p.Leu345Pro mutation within the 2B helix 6 was detected in a family that included 16 members suffering from gait disturbances caused by bilateral weakness in distal leg muscles that progressed to all limbs and bulbar, respiratory and facial muscles. 101 Many of the surviving patients were confined to a wheelchair or using a walker 7 to 20 years after disease onset.…”
Section: Cardiomyopathymentioning
confidence: 99%
See 3 more Smart Citations